Gregor and the marks of secret - Collins, Suzanne (London: Scholastic, 2013)
It's only a few months since Gregor and Boots returned from the Underland, leaving their mother behind to heal from the plague. Though Gregor's family receives frequent updates on her condition, they all know Gregor must return to fulfill his role as the warrior who is key to the Underlanders' survival.
Keywords: Children's stories